A review of the Neotropical genus Prionodera Chevrolat (Coleoptera, Chrysomelidae, Eumolpinae) with description of a new genus - Flowers, R. Wills (Zootaxa, 2004)
The genus Prionodera Chevrolat is redescribed and Prionodera adiastola new species (type locality: Limacocha, Ecuador), P. arimanes new species (type locality: Beni, Bolivia), P. dichroma new species (type locality: Panam , Panam ), P. esmeralda new species (type locality: Alajuela, Costa Rica), P. furcada new species (type locality: Ipeti, Panam ), P. gaiophanes new species (type locality: Limacocha, Ecuador), and P. nila new species (type locality: Panam , Panam ) are described and illustrated. The genera Stenolampra Baly and Jodasia Bechyn are placed in synonymy with Prionodera. Redescriptions are given for Prionodera costata (Baly) new combination, P. cyanea (Lef vre), P. geniculata (Baly) new combination, P. kirschi (Lef vre) new combination, P. lutea Erichson, P. marshalli Lef vre, P. merana Bechyn , P. bicolor (Olivier) and P. peruviana (Bechyn ) new combination. Jodasia roseometallica Bechyn is placed in synonymy with P. merana. The species chloroptera Lef vre and ocanana Lef vre are transferred from Prionodera to Metaxyonycha Chevrolat new combinations and the species nixa Bechyn is transferred from Prionodera to Prionoderita new genus. A key is given to the species in the revised genus Prionodera.Resumen. Se describe de nuevo el g nero Prionodera Chevrolat, y las especies nuevas Prionodera adiastola (localidad del tipo: Limacocha, Ecuador), P. arimanes (localidad del tipo: Beni, Bolivia) , P. dichroma (localidad del tipo: Panam , Panam ), P. esmeralda (localidad del tipo: Alajuela, Costa Rica), P. furcada (localidad del tipo: Ipeti, Panam ), P. gaiophanes (localidad del tipo: Limacocha, Ecuador), y P. nila (localidad del tipo: Panam , Panam ) son descritas y ilustradas. Los g neros Stenolampra Baly y Jodasia Bechyn son sinonomizados con Prionodera. Se presenta nuevas descripciones para Prionodera costata (Baly) combinaci n nueva, P. cyanea (Lef vre), P. geniculata (Baly) combinaci n nueva, P. kirschi (Lef vre) combinaci n nueva, P. lutea Erichson, P. marshalli Lef vre, P. merana Bechyn , P. bicolor (Olivier) and P. peruviana (Bechyn ) combi- naci n nueva. Jodasia roseometallica Bechyn es sinonomizado con P. merana. Las especies chloroptera Lef vre y ocanana Lef vre son transferidas de Prionodera a Metaxyonycha Chevrolat combinaci n nueva y la especie nixa Bechyn es transferida de Prionodera a Prionoderita g nero nuevo. Se presenta una clave a las especies en el g nero revisado Prionodera.